2018
DOI: 10.1007/s00205-018-1276-7
|View full text |Cite
|
Sign up to set email alerts
|

On Identifying Magnetized Anomalies Using Geomagnetic Monitoring

Abstract: We are concerned with the inverse problem of identifying magnetic anomalies with varing parameters beneath the Earth using geomagnetic monitoring. Observations of the change in Earth's magnetic field-the secular variation-provide information about the anomalies as well as their variations. In this paper, we rigorously establish the unique recovery results for this magnetic anomaly detection problem. We show that one can uniquely recover the locations, the variation parameters including the growth or decaying r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…We have (4.3) by using Lemma 4.1. Then by following the proof of Theorem 4.2 in [13] (see also Theorem 7.8 in [2]), one immediately has z (1) l = z (2) l , l = 1, 2, . .…”
Section: Unique Recovery Results For Magnetic Anomaly Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have (4.3) by using Lemma 4.1. Then by following the proof of Theorem 4.2 in [13] (see also Theorem 7.8 in [2]), one immediately has z (1) l = z (2) l , l = 1, 2, . .…”
Section: Unique Recovery Results For Magnetic Anomaly Detectionmentioning
confidence: 99%
“…We believe the strategy developed here can be extended to dealing with other coupled-physics inverse problems associated with coupled PDEs. This work is a continuation as well as an extension of our recent work [13] on the identification of magnetized anomalies using geomagnetic monitoring, which aims to establish a rigorous mathematical theory for the geomagnetic detection technology. The geomagnetic model considered in [13] is a linear Maxwell system, which is of different mathematical features from the magnetic system in this work.…”
Section: Concluding Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it is believed that one can establish the simultaneous recovery result in a certain general scenario, the uniqueness results in [7,12,14] were only established for certain restrictive configurations. We would also like to mention in passing that the simultaneous recovery of unknown medium parameters and internal sources were also considered for the electromagnetic wave phenomena arising from brain imaging [6] and geomagnetic detection technique [5]. It is readily observed that in the exterior measurement, the information of the unknown sound speed is coupled with that of the unknown source, and this makes the simultaneous recovery radically challenging.…”
Section: )mentioning
confidence: 99%
“…Over the past several decades, the inverse scattering problems with full measured data (both phase and intensity) have been mathematically and numerically studied intensively in the literature (see, e.g. the research monographs [1,13,23] and [14,15,34,35,53,54] for recently proposed interesting applications). Recently, a great deal of effort has been devoted to phaseless inverse scattering problems [2,5,6,24,25,29,30].…”
mentioning
confidence: 99%